Thinking Process Profiles of Senior High School Students in Solving Numeracy Problems across Different Levels of Self-Efficacy - Salman Alfarisi; Fatus Atho’ul Malik (Indonesian Journal of Applied Science and Technology, 2024)
This study aims to describe the thinking process profiles of high school students in solving numeracy problems from the perspective of self-efficacy. The study employed a qualitative, descriptive approach. The research subjects were six 11th-grade students at MA Ibadurrochman in Malang, selected through purposive sampling based on three categories of self-efficacy (high, moderate, and low). The instruments used included a self-efficacy questionnaire, a numeracy test equivalent to the Minimum Competency Assessment (AKM), and a semi-structured interview guide. Data analysis utilized the interactive model proposed by Miles, Huberman, and Saldaña. The results showed that students with high self-efficacy were able to fully complete all four stages of Polya’s problem-solving model: understanding the problem, planning a strategy, executing the plan, and checking the solution. Students with moderate self-efficacy were only able to master the understanding and planning stages and did not conduct a thorough review of their work. Students with low self-efficacy experienced significant obstacles starting from the problem-understanding stage, made procedural errors, and did not verify their answers at all. The conclusion of this study confirms that self-efficacy plays a crucial role in determining the quality of students’ thinking processes when solving numeracy problems.